Pengaruh Kepemilikan Manajerial Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Sebagai Moderasi - Muchamad Aprillia Salas (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
Firm value is an investor's perception of the company's success which is associated with stock prices. Several things that affect the value of the company include managerial share ownership, profitability, and corporate social responsibility. This study aims to analyze the effect of managerial ownership and profitability on firm value with corporate social responsibility as moderating. The population in this study were all mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2019. The number of samples in this study was 105 companies with 132 observational data. Sampling was carried out using purposive sampling and outlier methods, namely by using certain criteria and selection on the data for sample selection. The data analysis technique used in this research is Moderated Regression Analysis (MRA). Based on the results of this study indicate that managerial ownership and profitability have a significant effect on firm value. Based on the results of the study, it was also found that corporate social responsibility could not moderate managerial ownership and profitability on firm value.